Parents’ Understanding About First Aid In Early Childhood In Terms Of The Level Of Parents’ Education In Kelurahan Piyanggang, Kecamatan Sumowono, Kabupaten Semarang - Faqumala, Anisa Dwi; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2016)
Parents' understanding about first aid in early childhood is a level of parents' ability to understand the meaning, concepts, situations, facts about first aid of children that has been known and remembered before. The purpose of this study was to Determine differences in parental understanding of first aid in early childhood in terms of educational level of parents in the Village Piyanggang, Sumowono, District of Semarang. This research is using quantitative methods with the type of comparative research. The population in this study were all parents of children aged between 1-4 years. The sample in this study were 60 parents. The samples were selected using Purporsive sampling method. A method of the research using the data in scale understanding of first aid. The research is processed by comparisons of one-way ANOVA technique. This is demonstrated by the acquisition of the F calculate value <F table (45.076 <3.16) and the value of sig. > 0.05 (0.00 <0.05), then Ho denied. The result indicates that there are significant differences based on the level of education of elementary school with junior high school, elementary school with senior high school and than junior high school and senior high school.